Design and Development of a Low-Cost Programmable Air Regulator for Soft Pneumatic Actuators - Ritonga, Syahirul Alim; Sarah Iftin Atsani; Mohammad Ardyansah; Raditya Fadhil Arva; Herianto; Adrian Axel Yohannes (LPPM Politeknik Aceh Selatan, 2025)
Soft Pneumatic Actuators (SPAs) are widely utilized due to their affordability, simplicity, and ability to produce diverse movements such as bending and twisting by regulating air pressure. However, precise air pressure control remains a significant challenge in achieving desired actuator motions and maintaining performance consistency. While commercial programmable air regulators exist, their high cost often limits accessibility for budget-conscious research and educational institutions. This study addresses this challenge by designing and developing a low-cost programmable air regulator tailored for SPAs. Utilizing widely available and inexpensive components, the system aims to provide precise and reliable pressure control, democratizing SPA technology for researchers, small industries, and educational institutions. The regulator employs a stepper motor with a 1.8-degree step resolution and a 1:4 gear ratio, offering fine granularity in pressure adjustments. Carefully selected speed (1000 steps/s) and acceleration (500 steps/s) parameters ensure consistent operation under repetitive use. The program code of Arduino UNO microcontroller developed in this study can be readily adopted by researchers and practitioners. The regulator consistently achieves desired pressures through precise control of motor revolutions, proving to be a viable, cost-effective alternative to expensive commercial options.